The interplay between childhood obesity and vitamin D deficiency: mechanisms and implications - Zhou, Xiao; Chen, Yuhe; Xu, Jianxin; Li, Xiaobing; Wu, Yanmei; Xu, Lidan (Frontiers in Pediatrics, 2026)
Childhood obesity and vitamin D deficiency (VDD) are intertwined global health threats that amplify each other beyond their individual skeletal or metabolic consequences. This review synthesises a decade of clinical, translational and Mendelian-randomisation evidence to show that obesity drives VDD through volume dilution, adipose-tissue sequestration and metabolic associated steatotic liver disease (MASLD)-related hydroxylase dysfunction, while VDD in turn aggravates adipogenesis, leptin resistance and chronic low-grade inflammation, locking children into a self-perpetuating cycle. Meta-analysis of 12 randomised trials (n = 1,538) revealed that vitamin D supplementation improves insulin sensitivity and lowers systolic blood pressure only when baseline 25-hydroxyvitamin D (25(OH)D) is <20 ng/mL and systemic inflammation is modest; no consistent reduction in BMI or fat mass was observed. Obese youths require 2–3 times the standard dose to reach 30 ng/mL, yet incremental metabolic benefit plateaus near 4,000 IU/day and is lost when systemic inflammation is present. Precision-dosing algorithms incorporating VDR/CYP2R1/DBP genotypes and MASLD status are urgently needed. Multi-omic longitudinal trials should clarify the adipose-tissue threshold at which hepatic cytochrome P450 family 27 subfamily B member 1 (CYP27B1) becomes substrate-limited and evaluate the vascular safety of intermittent high-dose boluses before personalised supplementation is translated into routine paediatric practice.